Enhancing E-Commerce System Scalability Through Event-Driven Architecture with RabbitMQ and Docker - Rifqi Ramdhani; Alun Sujjada; Nugraha Nugraha (bit-Tech, 2025)
The rapid expansion of e-commerce in Indonesia has intensified the demand for highly scalable and responsive systems, especially during high-traffic periods. Traditional architectures that rely on synchronous Remote Procedure Call (RPC) models often experience performance bottlenecks, which can degrade user experience during peak load. To address this limitation, this study evaluates the use of an Event-Driven Design (EDD) architecture to improve system scalability and responsiveness. The objective is to compare the performance of RPC and EDD architectures using the "Add to Cart" feature an essential interaction in the e-commerce transaction flow as a benchmark. Two identical e-commerce prototypes were developed: one utilizing RPC and the other EDD, which incorporates asynchronous message processing. Performance testing was conducted using virtual users under multiple load scenarios to assess average response time and throughput. Results showed that the EDD-based system achieved up to 495 requests per second and maintained response times as low as 49–52 ms, whereas the RPC-based system peaked at only 5.1 requests per second with significant latency increases. These results represent a performance improvement of over 9,000% in throughput, confirming EDD's superiority in high-concurrency environments. This study contributes empirical evidence to the architectural decision-making process in e-commerce system design by demonstrating the substantial advantages of asynchronous, decoupled communication models. The findings support the adoption of EDD as a scalable and resilient solution for modern e-commerce platforms facing unpredictable traffic loads.